Does shifting from subsistence to commercial farming improve household nutrition and poverty? evidence from Malawi, Tanzania and Nigeria - Wisdom R Mgomezulu; Moses M.N Chitete; Beston B Maonga; Lovemore Kachingwe; Horace H Phiri; Mwayi Mambosasa; Lonjezo Folias (Research in Globalization, 2024)
The current study sought to assess the effect of smallholder crop commercialization on household nutrition security and poverty status. Recent government efforts have gone beyond investing in agricultural production, thereby establishing markets for smallholder farmers in order to commercialize the agricultural sector. As such, developing countries like Malawi, Tanzania, and Nigeria are slowly transitioning to a market economy in order to improve the livelihoods of their people. To that effect, the study used country-wide representative data from Malawi, Tanzania, and Nigeria collected under the World Bank Living Standards Measurement Surveys (LSMS) and employed an instrumented-censored (probit and tobit) model to solve for endogeneity bias. The results show that poverty and nutrition insecurity were higher among subsistence farmers, emphasizing the need for a shift towards commercialization of the country's agricultural sector. Furthermore, farmer social and institutional context significantly influenced market participation. The study hence recommends a tailor-made extension delivery system, cutting across gender divides and other social barriers among smallholder farm households, in order to improve crop production among subsistence farmers, ensure household food security, and increase income from the sale of surplus crop output.